INTEGRASI PROGRAM SEKOLAH PRASAJA SEJATI PADA MATA PELAJARAN BAHASA JAWA - Yatmanto; Daryanti (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
In the modern era, where foreign languages increasingly dominate, regional languages such as Javanese are becoming marginalized. However, local languages are essential as markers of identity and vehicles for transmitting cultural values. This study aims to evaluate the program's impact on students' Javanese language skills and the internalization of politeness and communication ethics as part of character education aligned with the Pancasila student profile.This research employed a qualitative approach using a case study method. The variables examined include students' ability to use the Javanese language and their understanding of traditional etiquette. The data focused on students in grades IV to VI, teachers, and parents at SD Negeri 3 Bulukerto. Data were collected through participatory observation, questionnaires, in-depth interviews, and Focus Group Discussions (FGD). Thematic analysis was used to interpret the collected data and identify emerging patterns.The findings indicate that the Prasaja Sejati program significantly improved students’ use of krama Javanese in daily interactions both at school and at home. Thematic analysis revealed enhanced student awareness of politeness norms inherent in Javanese culture and increased collaboration between the school, parents, and the community. These results demonstrate that the program impacts not only students’ linguistic abilities but also their cultural and character development. The program is recommended as a culturally grounded educational model that can be adopted by other schools to promote local identity amid increasing globalization and digitalization.